Globally stabilizing feedback control of nonlinear switched systems with time delays - Xu, Honglei; Zhang, Y. (2015)
In this paper, we study the problem of stabilizability of the nonlinear switched system with time-delay in switching signal. Firstly, some new concepts of locally and globally asymptotical or exponential stabilizability with respect to state feedback and switching law are given and then, using the method of Lyapunov function and delay inequalities, some sufficient conditions are obtained which can guarantee the resulting closed-loop switched systems are locally or globally asymptotically stable and exponentially stable.